2005
DOI: 10.1038/sj.npp.1300922
|View full text |Cite
|
Sign up to set email alerts
|

Administration of the D2 Dopamine Receptor Antagonist Sulpiride into the Shell, but not the Core, of the Nucleus Accumbens Attenuates Cocaine Priming-Induced Reinstatement of Drug Seeking

Abstract: Enhanced dopamine transmission in the nucleus accumbens plays an important role in cocaine priming-induced reinstatement of drugseeking behavior. However, the contribution of each dopamine receptor subtype to this behavior remains unclear. The present experiments were designed to assess the role of D2-like dopamine receptors in the nucleus accumbens core and shell subregions in cocaine priming-induced reinstatement of drug seeking. Rats were trained to lever press for cocaine using a fixed ratio (FR) 5 schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
74
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 49 publications
8
74
0
Order By: Relevance
“…Since the accumbens core and shell are relatively small and adjacent nuclei, it is possible that the effect of intra-core AP-5 was due to lateral diffusion into the shell. While this explanation cannot be ruled out, it is important to note that the procedures used here were similar or identical to previous studies that demonstrated clear and statistically significant functional differences between the core and shell subregions of the nucleus accumbens [2,3,15,23,28,37].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 53%
See 3 more Smart Citations
“…Since the accumbens core and shell are relatively small and adjacent nuclei, it is possible that the effect of intra-core AP-5 was due to lateral diffusion into the shell. While this explanation cannot be ruled out, it is important to note that the procedures used here were similar or identical to previous studies that demonstrated clear and statistically significant functional differences between the core and shell subregions of the nucleus accumbens [2,3,15,23,28,37].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 53%
“…In contrast, the core is more involved in the compulsivity of drug addiction [16] and the effects of drug-associated cues [14,18,25]. In terms of cocaine priming-induced reinstatement of drug seeking, dopamine receptors play differential roles in the shell versus the core [2][3][4]. For example, infusion of dopamine receptor antagonists into the accumbens shell, but not the core, attenuates the reinstatement of cocaine-seeking behavior [2][3][4].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic administration or local NAc microinjection of DA agonists reinstate, whereas DA antagonists block, reinstatement of cocaine-seeking behavior (Shalev et al, 2002;Anderson et al, 2003Anderson et al, , 2006Bachtell et al, 2005). Endocannabinoids appear uninvolved in such DAdependent drug-primed relapse, because CB 1 receptor blockade by SR141716A fails to block cocaine-or heroin-induced increases in NAc DA in drug-naive rats (Tanda et al, 1997;Caillé and Parsons, 2006).…”
Section: Introductionmentioning
confidence: 99%